2017
DOI: 10.9758/cpn.2017.15.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of a Shorter Time to Hospitalization in Patients with Bipolar Disorder: Medication during the Acute and Maintenance Phases and Other Clinical Factors

Abstract: ObjectiveThe present study was conducted to compare the effects of pharmacological treatments during the acute and maintenance phases of mood episodes, sociodemographic, and clinical characteristics between a shorter time to hospitalization group (<12 months) and a longer time to hospitalization group (≥12 months).MethodsThe discharge medication for the first hospitalization was considered the acute treatment and the medication used during the week prior to the second hospitalization at the outpatient clinic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Analysis of factors other than drugs of interest showed that the inpatient meta‐visit had an RR of 1.68 over the outpatient meta‐visit for psychiatric hospitalization ( P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD . Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of factors other than drugs of interest showed that the inpatient meta‐visit had an RR of 1.68 over the outpatient meta‐visit for psychiatric hospitalization ( P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD . Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD .…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of factors other than drugs of interest showed that the inpatient meta-visit had an RR of 1.68 over the outpatient metavisit for psychiatric hospitalization (P < 2.23 × 10 −308 ), supporting the evidence that previous hospitalization is a strong predictor of subsequent hospital admission in patients with BD. [29][30][31][32][33] Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD. 30 The findings on the reduced risk of psychiatric hospitalizations for patients on antibiotics and non-steroidal anti-inflammatory drugs contribute to the evidence suggesting the importance of immune alterations, inflammation, and the microbiome in BDs.…”
Section: × 10 −12supporting
confidence: 90%
“…However, other guidelines recommend MS or AAP monotherapy and combination therapy as a first-line modality in a same degree while MS+AAP combination therapy was ranked as TOC in KMAP-BP 2018. This might reflect that Korean experts were doubtful for the clinical effectiveness of mono-therapy and had laid stress on the superiority of combination therapy over monotherapy in terms of efficacy for mania based on results from the clinical trials and meta-analysis 3944)…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a MS and an AD was recommended as the first-line treatment in KMAP-BP 2014, but the recommendation for this combination is downgraded to second-line in this revision. Evidence does not support the use of ADs in patients with bipolar depression 33 , 34) and it remains controversial. 35) The changes in the recommendation level for AD use in the KMAP-BP 2018 might reflect that all evidence-based guidelines consistently recommend limited use of ADs adjunctively with anti-manic agents in cases when ADs are needed.…”
Section: Discussionmentioning
confidence: 99%